RANCANG BANGUN SISTEM INFORMASI PENJUALAN BARANG CV. FENNY DENGAN METODE WATERFALL - Rosyida, Susy (Jurnal EDik Informatika, 2021)
CV Fenny is a business or a trading business in the field of food or daily necessities. CV information system. Fenny still uses a manual system, inversely proportional to increase the number of customers and increasing sales turnover. Therefore, as a consequence, the information needs cannot or is not fulfilled and result in an increase in the performance of CV employees. Fenny is difficult to achieve in meeting consumer demand. Because the data collection was not structured and found some duplicate data. Storing and retrieval of transaction data have not been neatly arranged, because it only relies on a manual recording, and the storage is still using file cabinets which result in the accumulation of documents, and as a result, it is difficult to recover old transaction data if needed. The process of making sales data reports less accurate, fast, and perfect because you have to collect all the transactions that occur first, as a result, it will take longer. The method used in designing the sales and information system CV. Fenny uses the waterfall method. Making a sales system CV. Fenny, is expected to solve existing constraints, simplify, speed up the sales system, and hopefully increase the profit from selling goods on the CV. Fenny.